Pengaruh Pendekatan Open-Ended Dan Motivasi Belajar Terhadap Kemampuan Berpikir Kreatif Siswa - Nur 'Afifah (Balai Diklat Keagamaan Medan, 2021)
The objectives of this research : (1) to study the influence of teaching by open-ended approach to the creative thinking capability of student, (2) to study the influence of learning motivation to the creative thinking capability of student, (3) to study whether there is or not interaction between the learning approach by student learning motivation in influence the creative thinking capability of student. This research is a quasi experiment that conducted at SMP Swasta Dharma Bakti Lubuk Pakam (Private Junior High School). The sample for experiment and control groups were took by random sampling. The sample of research is 58 students that consist of from the Grade VII for 30 student as experiment class and from Grade VIIb for 28 students as control class. Variables in this research is learning approach that consist of open-ended approach and expository as active independent variable and student learning motivation that consist of higher, medium, lower learning motivation as moderator variable, creative thinking capability of student as dependent variable. The applied instrument in this research are (1) creative thinking capability test, (2) questioner of learning motivation. While instrument in this research to measure the creative thinking capability of student is a essay test with 5 test item and reliability coefficient is 0.829 (higher) The data of student learning motivation was collected by questionnaire with 30 items that adopted from Sembiring. Before the implementation of analysis method, its analysis requirement is tested by normality and homogeneity test. Normality is tested by Liliefors test while homogeneity is tested by Barlett test (data processing by SPSS 20). The method of data analysis is Anova with two path on significant level α = 0.05 that continued by Scheffee test. The teaching instrument are (1) Teaching Implementation plan (RPP), (2) Student Activity test, (3) Book of Student. The test of problem solving is essay test focused to the creativity. The data in this research is analyzed by using descriptive statistic analysis and inferential analysis. The descriptive analysis is aimed to describe the creative thinking capability, learning motivation of student and student activity in teaching learning process. While the inferential statistic analysis is used to study whether there is a difference in the creative thinking capability of student that taught by open ended approach and the student taught by expository approach. The results of research indicated that (1) there is a difference in creative thinking capability of student who taught by open-ended approach to the student who taught by expository approach. The student taught by open ended approach have a student creative thinking capability with that higher than student whoi taught by expository approach with ; it get Fcalculated = 124.44 > Ftable = 4.01; (2) there is a difference in creative thinking capability between student with the higher, medium and lower learning motivation. The average of student cretive thinking capability with the higher learning motivation is higher than student with the medium learning motivation and higher than student with the lower learning motivation in which Fcalculated = 143.869 > Ftabgle = 3.16. Based on the data analysis is concluded that the student creative thinking capability that taught by open ended approach is higher than student that taught by expository approach. According to the characteristics of student, the student creative thinking capability with the higher learning motivation is higher than student with the medium learning motivation and higher than student with the lower learning motivation.